Uric Acid and Atherosclerosis in Patients with Chronic Kidney Disease: Recent Progress, Mechanisms, and Prospect - Yuchu Liu; Zeyu Li; Yuanwen Xu; Haiping Mao; Naya Huang (Kidney Diseases)
Background: Chronic kidney disease (CKD) is a prevalent global health concern, significantly linked to increased cardiovascular morbidity and mortality. Among various risk factors, uric acid (UA) has emerged as a potentially modifiable contributor to cardiovascular complications in CKD patients. Summary: Elevated serum uric acid levels frequently occur in individuals with CKD and are associated with the development of atherosclerosis (AS). Uric acid has been demonstrated to exacerbate inflammatory processes, promote oxidative stress, and cause endothelial dysfunction, which are critical factors that drive the formation of atherosclerotic plaques. Furthermore, high uric acid levels can worsen renal function, establishing a detrimental cycle that amplifies cardiovascular risk. Key Messages: This review investigates the complex interconnection between UA and AS in patients with CKD, highlighting the underlying mechanisms and therapeutic considerations. A more profound comprehension of this relationship is essential for enhancing cardiovascular health and outcomes in this vulnerable population.